Tuberculosis vaccines and therapeutic drug: challenges and future directions - Yajing An; Ruizi Ni; Li Zhuang; Ling Yang; Zhaoyang Ye; Linsheng Li; Seppo Parkkila; Ashok Aspatwar; Wenping Gong (Molecular Biomedicine)
Abstract Tuberculosis (TB) remains a prominent global health challenge, with the World Health Organization documenting over 1 million annual fatalities. Despite the deployment of the Bacille Calmette-Guérin (BCG) vaccine and available therapeutic agents, the escalation of drug-resistant Mycobacterium tuberculosis strains underscores the pressing need for more efficacious vaccines and treatments. This review meticulously maps out the contemporary landscape of TB vaccine development, with a focus on antigen identification, clinical trial progress, and the obstacles and future trajectories in vaccine research. We spotlight innovative approaches, such as multi-antigen vaccines and mRNA technology platforms. Furthermore, the review delves into current TB therapeutics, particularly for multidrug-resistant tuberculosis (MDR-TB), exploring promising agents like bedaquiline (BDQ) and delamanid (DLM), as well as the potential of host-directed therapies. The hurdles in TB vaccine and therapeutic development encompass overcoming antigen diversity, enhancing vaccine effectiveness across diverse populations, and advancing novel vaccine platforms. Future initiatives emphasize combinatorial strategies, the development of anti-TB compounds targeting novel pathways, and personalized medicine for TB treatment and prevention. Despite notable advances, persistent challenges such as diagnostic failures and protracted treatment regimens continue to impede progress. This work aims to steer future research endeavors toward groundbreaking TB vaccines and therapeutic agents, providing crucial insights for enhancing TB prevention and treatment strategies.